2019
DOI: 10.1111/ejn.14607
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety‐like behavior in female mice changes by feeding, possible effect of guanylate cyclase C

Abstract: Anxiety disorders are the most frequent mental disorders and are more prevalent in the female population. Up to date, an involvement of guanylate cyclase A and B in anxiety‐like behavior has been suggested. In this study, we showed an expression of guanylate cyclase C (GC‐C) in the amygdala which is regulated by feeding. Therefore, we further investigated sex differences of GC‐C effects on anxiety levels with special attention to female estrous cycle and feeding. The effects of estrous cycle and feeding were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…For example, authors determined the expression of estrogen receptors in the brainstem ( 22 ) without separating the female rats by estrous phase, although receptors expression changes during the estrous cycle ( 23 ). Our previous study also showed a difference in expression regulation of guanylate cyclase C in the amygdala and hypothalamus during the estrous cycle ( 2 ). Results such as these emphasize the importance of determining the phase of the estrous cycle in any study involving female animals.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, authors determined the expression of estrogen receptors in the brainstem ( 22 ) without separating the female rats by estrous phase, although receptors expression changes during the estrous cycle ( 23 ). Our previous study also showed a difference in expression regulation of guanylate cyclase C in the amygdala and hypothalamus during the estrous cycle ( 2 ). Results such as these emphasize the importance of determining the phase of the estrous cycle in any study involving female animals.…”
Section: Discussionmentioning
confidence: 75%
“…Performing experiments just to meet a requirement yields misleading conclusions and scientifically meaningless results. It is especially important that female animals are in the same phase of their estrous cycles because of a different effect of estrogen and progesterone on numerous physiological and pathological conditions ( 2 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, research of effects of UGN/GC-C signaling pathway in the brain and their role in metabolism became a hot topic. GC-C was shown in the rodent brain in neurons of the cerebral cortex, amygdala, midbrain, hypothalamus and Purkinje cells and neurons of deep nuclei of the cerebellum, but also confirmed in the human hypothalamus and prefrontal cortex [33][34][35][36][37][38][39].…”
Section: Gps and Gc-c In The Brainmentioning
confidence: 99%
“…Wright et al discuss the need for an integrated translational approach in understanding the neuroscience of social vigilance and social anxiety in adolescent males and females in order to develop effective strategies for treatments (Wright et al, 2019). In keeping with the importance of translational research, Dugandzic et al use a rodent model in their article to show that guanylate cyclase C activation in the amygdala, which is enhanced with feeding (2h after a meal) only in females, is important in the regulation of anxiety-like behaviors and may be an important factor in understanding sex difference in the incidence of anxiety disorders in humans (Dugandzic et al, 2019). Moreover, Fontana et al, report that female zebrafish have higher anxiety-like behavior than males, making zebrafish a valuable model for further understanding the neuroscience of sex differences in anxiety and related disorders (Fontana et al, 2019).…”
Section: Accepted Articlementioning
confidence: 99%